Can we end the cold war?; Study in American foreign policy - Perla, Leo (New York, 1960)
This is a challenging and timely book. In this era of world revolu tion it extends the boundaries of our thinking beyond the mechanics of disarmament to a moral imperative which is the only sure basis of a world community. That imperative is a single standard of morals for nations as for individuals. With convincing argument, richly documented from history, the case is made against that double standard which distorts and falsifies human relationships by projecting the strategy of war into the conditions of peace. The fallacy of such shadowy reflections of Machiavellian policy is evi dent in any such analysis of politics as this, yet it continues to find support in both academic and political circles. The reason for this, the one which lies in the background of this survey, is the fact that down to the present, the final argument of nations, as formerly of kings and princes, has been war and that in a world of real or poten tial enemies there can be no true community of interest. The double standard is the strategy of an insecure world.
Keywords: o